Pengaruh Skills Keterampilan dan Abilities Kemampuan Terhadap Produktivitas Kerja Karyawan PT. Bastian Olah Sawit Simpang Tungkal - Eti Pinasti; Kholilah Kholilah; Mister Candera (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2025)
The purpose of this Study was to determine the effect of skills and work abilities on employee work productivity at PT. Bastian Olah Sawit Simpang Tungkal? I simultaneously and partially. This study is a associative study, the variables used are skills, abilities on employee work productivity. The populationin this study was 133 employees taken as many as 58 samples. Primary data needed as a basis for analysis, while the data collection technique was a questionnaire, the analysis technique used was multiple linear regression, hypothesis testing. f-fees ,t-test and coofecient of determination. The results of this study are:there is a significant influence of skills and abilities on the work productivity of employees of PT. Bastian Olah Sawit Simpang Tungkal. there is a significant influence of skills on the work productivity of employees of PT. Bastian Olah Sawit Simpang Tungkal. there is a significant influence of abilities on the work productivity of employees of PT. Bastian Olah Sawit Simpang Tungkal. As evidenced by the calculated t value being smaller that the t table